A preservação da paisagem e a conservação da natureza no III Reich - Antonio Carlos Vitte (Confins)
The main goal of this article is to discuss the landscape preservation and nature conservation policies during the Nazi regime (1933-1945) in Germany taking for granted that the III Reich, had appropriated and transformed ideologically the romantic ideology relations between nature and culture. These policies were based on the authoritarian conception that nature was the home (Heimat) of Germanic civilization. The Nazi regime produced a symbiosis, between the concepts of Landschaft and Lebensraum, which manifested the regional division of Germany itself.